2014
DOI: 10.1002/jhbp.132
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin as a useful biomarker for determining the need to perform emergency biliary drainage in cases of acute cholangitis

Abstract: Acute cholangitis with high PCT levels can signify the need to perform emergency biliary drainage and institute intensive care even if categorized by TG13 as not being severe cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 22 publications
1
45
2
1
Order By: Relevance
“…Shinya et al. recently demonstrated that applying the TG13 severity assessment criteria resulted in underestimating of the severity of several AC cases as mild to moderate that would have been as severe AC based on positive blood culture results for bacteremia and/or positive for purulent bile draining from the duodenal papilla, and their findings are consistent with the results of the present study. We concluded that underestimation of severity of AC in patients who require urgent/early biliary drainage as mild AC is a shortcoming of the severity assessment criteria of the TG13.…”
Section: Discussionsupporting
confidence: 91%
“…Shinya et al. recently demonstrated that applying the TG13 severity assessment criteria resulted in underestimating of the severity of several AC cases as mild to moderate that would have been as severe AC based on positive blood culture results for bacteremia and/or positive for purulent bile draining from the duodenal papilla, and their findings are consistent with the results of the present study. We concluded that underestimation of severity of AC in patients who require urgent/early biliary drainage as mild AC is a shortcoming of the severity assessment criteria of the TG13.…”
Section: Discussionsupporting
confidence: 91%
“…In that study, both PCT and CRP levels were significantly higher in patients with severe cholangitis, although PCT yielded a significantly higher AUC value for predicting severe cholangitis (24). In contrast to CRP, PCT levels increase in the context of a bacterial infection, and thus PCT is a sensitive marker for detecting early sepsis with bile duct inflammation (24). Although the PCT test can be used routinely at the time of ED admission and results can be obtained in approximately 30 min (24), it is expensive and therefore difficult to obtain serial measurements of both PCT and CRP (20).…”
Section: Discussionmentioning
confidence: 84%
“…As procalcitonin (PCT) and CRP have been widely used as critical care biomarkers (20), Shinya et al (24) investigated the usefulness of these markers, as well as the WBC, as biomarkers of inflammation in patients with acute cholangitis at the time of admission. In that study, both PCT and CRP levels were significantly higher in patients with severe cholangitis, although PCT yielded a significantly higher AUC value for predicting severe cholangitis (24). In contrast to CRP, PCT levels increase in the context of a bacterial infection, and thus PCT is a sensitive marker for detecting early sepsis with bile duct inflammation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Shinya et al. reported that the PCT level in patients with severe cholangitis was higher than that in patients with mild cholangitis. However, these biomarkers do not reflect the immunosuppression status of all individuals.…”
Section: Introductionmentioning
confidence: 98%